2017
DOI: 10.3390/genes8040124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Complete Chloroplast Genome of Four Endangered Herbals of Notopterygium

Abstract: Notopterygium H. de Boissieu (Apiaceae) is an endangered perennial herb endemic to China. A good knowledge of phylogenetic evolution and population genomics is conducive to the establishment of effective management and conservation strategies of the genus Notopterygium. In this study, the complete chloroplast (cp) genomes of four Notopterygium species (N. incisum C. C. Ting ex H. T. Chang, N. oviforme R. H. Shan, N. franchetii H. de Boissieu and N. forrestii H. Wolff) were assembled and characterized using nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 83 publications
8
36
0
Order By: Relevance
“…Higher nucleotide diversity has been found in SCs compared with IRs and in noncoding regions compared with coding regions, which is in accordance with the results found for other taxa [43][44][45]63,68], although exceptions have been identified [32,69]. A cp genome has a copy-dependent repair mechanism that ensures the uniformity and stability of two IR regions in sequence and enhances the stability and conservation of the genome [70,71], which might explain the lower sequence divergence in the IRs compared with the LSC or SSC regions, because natural selection coding regions are more conserved than non-coding regions [72].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher nucleotide diversity has been found in SCs compared with IRs and in noncoding regions compared with coding regions, which is in accordance with the results found for other taxa [43][44][45]63,68], although exceptions have been identified [32,69]. A cp genome has a copy-dependent repair mechanism that ensures the uniformity and stability of two IR regions in sequence and enhances the stability and conservation of the genome [70,71], which might explain the lower sequence divergence in the IRs compared with the LSC or SSC regions, because natural selection coding regions are more conserved than non-coding regions [72].…”
Section: Discussionsupporting
confidence: 89%
“…In subsequent studies, the main challenge in oak classification will be infrasectional classification. With the rapid development of sequencing technology, genomic databases are becoming increasingly vital for in-depth studies of plant phylogenetics [31,32]. However, due to the use of plastid and nuclear data, incongruent phylogenies have been observed in not only Quercus but also other genera [33][34][35].…”
mentioning
confidence: 99%
“…Previously, it was identified that the alignment of many genomes contributes and identifies mutational hotspots, which are widely used for interspecies discrimination and species-level phylogenetic studies [52]. The coding region in many previous studies has been proven to play an important role in species-level phylogenetic analyses like some of the genes, such as ycf1 in Anemopaegma [53] and rps16, psaI, psbT, psbH, petB, rpoA, and rps11 in Notopterygium [54], which were more divergent than non-coding regions.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results indicated that the nrITS may be affected by hybridization and incomplete lineage sorting. Plastid DNA, which is maternally inherited, is longer and has less mutation than the nuclear ITS region, so it will provide more phylogenetic information and not be interfered with by paralogous genes in the phylogenetic studies [23,78]. Therefore, plastid DNA can better reflect the evolutionary relationship.…”
Section: Phylogenetic Analysismentioning
confidence: 99%